Synthesis and physical-chemical properties of 3-alkylthio-5-(quinoline-2-yl, 2-hydroxyquinoline- 4-yl)-4-R-2,4-dihydro-3H-1,2,4-triazoles - Kaplaushenko, T. M.; Panasenko, O. I.; Каплаушенко, Т. Н.; Панасенко, А. И.; Каплаушенко, Тетяна Миколаївна; Панасенко, Олександр Іванович (Запорізький державний медичний університет, 2016)
The major social and economic problem of pharmaceutical industry is the search for biologically active substances, which may become the basis of new drugs, competitive with expensive imported drugs. Analysis of literature shows that in recent decades the attention is paid to researches of heterocyclic systems as potential biologically active agents of both domestic and foreign scientists. Particular interest in this regard cause 3-thio derivatives of 1,2,4-triazoles. Despite high number of publications relating to synthesis and biological properties of 1,2,4-triazole derivatives, the structure and physical-chemical properties of these compounds are studied insufficiently. In this regard, the study of synthetic, physical-chemical and biological properties of 3-alkylthio-5-(quinoline-2-yl, 2-hydroxyquinoline-4-yl)-4-R1-2,4-dihydro-3H-1,2,4-triazoles in our point of view is a new, theoretically and practically significant direction. Purpose - targeted synthesis of new low-toxic and highly effective compounds with potential pharmacological activity in a series of 3-alkylthio-5-(quinoline-2-yl, 2-hydroxyquinoline-4-yl)-4-R-2,4-dihydro-3H-1,2,4-triazoles and the study of physical and chemical properties of the synthesized compounds. Materials and methods. As starting compounds 5-(quinoline-2-il- 2-hydroxyquinoline-4-yl)-4-R1-3-thio-1,2,4-triazoles have been used. Through further cooperation with halogen alkanes (ethyl bromide, propyl bromide, amyl bromide, octyl bromide, nonyl bromide, decyl bromide, cyclohexyl chloride, benzyl chloride) 3-alkylthio-5-(quinoline-2-yl, 2-hydroxyquinoline-4-yl)-4-R1-2,4-dyhidro-3H-1,2,4-triazoles have been obtained. Results. 15 New compounds have been received as a result of synthetic transformations, the structure of synthesized compounds has been confirmed by modern complex of physical and chemical methods of analysis (IR-spectrophotometry, 1H NMR-spectroscopy, elemental analysis), and their individuality has been proved by thin layer chromatography. Conclusions. While synthetic and physical-chemical researches, the preparative methods of synthesis of 3-alkylthio-5-(quinoline-2-yl, 2-hydroxyquinoline-4-yl -4-R-2,4-dihydro-3H-1,2,4-triazoles have been developed, the structure of the synthesized compounds has been installed and finally confi rmed. Пошук речовин із високими показниками біологічної дії, що можуть стати основою нових лікарських засобів, які були б конкурентоспроможні з дорогими імпортними препаратами, є одним із найважливіших соціальних та економічних завдань фармацевтичної галузі. Аналіз наукових літературних джерел засвідчує: в останні декілька десятиліть особливу увагу привертають роботи як вітчизняних, так і закордонних учених, які працюють над дослідженням гетероциклічних систем як потенційних біологічно активних агентів. Особливу зацікавленість у цьому плані викликають 3-тіопохідні 1,2,4-тріазолу. Незважаючи на велику кількість публікацій стосовно синтезу та біологічних властивостей похідних 1,2,4-тріазолу, недостатньо вивченими, на наш погляд, є будова та фізико-хімічні властивості цих сполук. Отже, вивчення синтетичних, фізико-хімічних і біологічних властивостей 3-тіо-похідних 5-(хінолін-2-іл, 2-гідроксихінолін-4-іл)-4-R-2,4-дигідро-3Н-1,2,4-тріазол-3-тіонів, на наш погляд, має наукову новизну, теоретичну та практичну значущість. Мета роботи – цілеспрямований синтез нових малотоксичних і високоефективних сполук із потенційними видами фармакологічної активності в ряду 3-алкілтіо-5-(хінолін-2-іл, 2-гідроксихінолін-4-іл)-4-R-2,4-дигідро-3Н-1,2,4-тріазолів, вивчення фізико-хімічних властивостей синтезованих сполук. Матеріали та методи. Як вихідні сполуки використали 5-(хінолін-2-іл-, 2-гідроксихінолін-4-іл)-4-R1-3-тіо-1,2,4-тріазоли, з них шляхом дальшої взаємодії з галоїдними алканами (етилбромід, пропілбромід, амілбромід, октилбромід, нонілбромід, децилбромід, циклогексилхлорид, бензилхлорид) отримали 3-алкілтіо-5-(хінолін-2-іл, 2-гідроксихінолін-4-іл)-4-R-2,4-дигідро-3Н-1,2,4-тріазоли. Результати. У результаті синтетичних перетворень отримано 15 нових сполук, будову яких підтверджено за допомогою комплексу сучасних фізико-хімічних методів аналізу (ІЧ-спектрофотометрії, 1Н ЯМР-спектроскопії, елементного аналізу), а їхню індивідуальність – методом тонкошарової хроматографії. Висновки. Під час синтетичних і фізико-хімічних досліджень розроблено препаративні методики синтезу 3-алкілтіо-5-(хінолін-2-іл, 2-гідроксихінолін-4-іл)-4-R-2,4-дигідро-3Н-1,2,4-тріазолів, встановлено та остаточно підтверджено будову всіх синтезованих сполук. Поиск веществ с высокими показателями биологического действия, которые могут стать основой новых лекарственных средств, конкурентоспособных наряду с дорогими импортными препаратами, является одной из важнейших социальных и экономических задач фармацевтической отрасли. Анализ научных литературных источников показывает, что в последние несколько десятилетий особое внимание привлекают работы как отечественных, так и зарубежных учёных, работающих над исследованием гетероциклических систем как потенциальных биологически активных агентов. Особый интерес в этом плане вызывают 3-тиопроизводные 1,2,4-триазола. Несмотря на значительное количество публикаций по синтезу и биологической активности производных 1,2,4-триазола, недостаточно изученными, с нашей точки зрения, являются строение и физико-химические свойства этих соединений. В связи с этим изучение синтетических, физико-химических и биологических свойств 3-тио-производных 5-(хинолин-2-ил, 2-гидроксихинолин-4-ил)-4-R- 2,4-дигидро-3Н-1,2,4-триазол-3-тионов, с нашей точки зрения, имеет научную новизну, теоретическую и практическую значимость. Цель работы – целенаправленный синтез новых малотоксичных и высокоэффективных соединений с потенциальными видами фармакологической активности в ряду 3-алкилтио-5-(хинолин-2-ил, 2-гидрокси-4-ил)-4-R-2,4-дигидро-3Н-1,2,4-триазолов, а также изучение физико-химических свойств синтезированных соединений. Материалы и методы. В качестве исходных соединений были использованы 5-(хинолин-2-ил, 2-гидрокси-4-ил)-4-R1-3-алкилтио-1,2,4- триазол-3-тионы, из которых путём дальнейшего взаимодействия с галоидными алканами (этилбромид, пропилбромид, амилбромид, октилбромид, нонилбромид, децилбромид, циклогексилхлорид, бензилхлорид) были получены 3-алкилтио-5 (хинолин-2-ил, 2-гидрокси- 4-ил) -4-R-2,4-дигидро- 3Н-1,2,4-триазолы. Результаты. В результате синтетических преобразований получено 15 новых соединений, строение которых подтверждено с помощью комплекса современных физико-химических методов анализа (ИК-спектрофотометрии, 1Н ЯМР-спектроскопии, элементного анализа), а их индивидуальность – методом тонкослойной хроматографии. Выводы. Во время синтетических и физико-химических исследований разработаны препаративные методики синтеза 3-алкилтио-5-(хинолин-2-ил, 2-гидрокси-4-ил)-4-R-2,4-дигидро-3Н-1,2,4-триазолов, установлено и окончательно подтверждено строение всех синтезированных соединений.
Синтез і фізико-хімічні властивості 3-алкілтіо-5-(хінолін-2-іл, 2-гідроксихінолін-4-іл)-4-R-2,4-дигідро-3Н-1,2,4-тріазолів
Синтез и физико-химические свойства 3-алкилтио-5-(хинолин-2-ил, 2-гидрокси-4-ил)-4-R-2,4-дигидро-3Н-1,2,4-триазолов
Keywords: 1,2,4-triazole; Synthesis; Physical-Chemical Properties; 1,2,4-тріазол; синтез; фізико-хімічні властивості; 1,2,4-тріазол; Синтез; фізико-хімічні властивості